Eyelid Crease Height Affects the Evaluation of Age-related Changes in the Eyelids - Shinsuke Akita, MD, PhD (Wolters Kluwer, 2021)
Background:. Although the functional and anatomical differences between the left and right eyelids are important in the evaluation of age-related changes in the eyelids, they have not been described clearly as indications for surgical treatments. This study aimed to investigate how laterality of the eyelids affects evaluation of age-related changes. Methods:. Photographs of either one or both eyelids of 100 people were evaluated in four stages by 10 plastic surgeons. To investigate the consistency of the results between evaluations, surgeons evaluated the single-eyelid photographs (group U) or two-eyelid photographs (group B). It was investigated whether the difference in margin reflex distance 1, height of the upper eyelid crease, height of eyebrow, and levator contractile function were associated with mismatched evaluations. Results:. The weighted kappa coefficient for groups B and U was 0.77 (substantial agreement). One-point difference in scores was observed in 23 cases. In the multiple logistic regression analysis, only the laterality the height of the eyelid crease was significantly different between patients whose evaluations were matched and those whose evaluations were mismatched (0.9 ± 0.1 mm versus 1.7 ± 0.2 mm; OR = 1.06, 95%CI: 1.01–1.10; P = 0.01). Conclusions:. Besides the structure and function of each eyelid, the laterality of the height of the eyelid crease was important in the evaluation of the age-related changes in the eyelids. This factor may be important in evaluating the aesthetic and visual impressions of age-related changes in the eyelids.